2004
DOI: 10.1002/pssb.200405225
|View full text |Cite
|
Sign up to set email alerts
|

Hydrostatic pressure effects on the donor impurity‐related photoionization cross‐section in cylindrical‐shaped GaAs/GaAlAs quantum well wires

Abstract: Using a variational method the binding energy has been calculated for a shallow donor impurity and the donor-related photoionization cross-section in 1D and 0D GaAs low-dimensional systems. The dependence on the binding energy and the photoionization cross-section for a hydrogenic donor impurity in the finite potential model are discussed and the results are presented as a function of the radius, polarization of the photon, applied hydrostatic pressure, and photon energy. The calculations for the pressure effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…These studies have considered the donor and acceptor impurity binding energies and density of impurity states (DOIS) in various geometries of the above-mentioned nanostructures. The hydrostatic pressure, uniaxial stress, and electric field effects, in the low temperature regime (close to 4 K), have been reported for donor impurities in single QWs [10][11][12], symmetrical and asymmetrical double quantum wells (DQW) [13,14], QWWs [15,16] and GaAs QDs [17][18][19]. As a general feature, the studies show that the binding energy of a donor electron is enhanced by increasing the hydrostatic pressure and the uniaxial stress.…”
Section: Introductionmentioning
confidence: 87%
“…These studies have considered the donor and acceptor impurity binding energies and density of impurity states (DOIS) in various geometries of the above-mentioned nanostructures. The hydrostatic pressure, uniaxial stress, and electric field effects, in the low temperature regime (close to 4 K), have been reported for donor impurities in single QWs [10][11][12], symmetrical and asymmetrical double quantum wells (DQW) [13,14], QWWs [15,16] and GaAs QDs [17][18][19]. As a general feature, the studies show that the binding energy of a donor electron is enhanced by increasing the hydrostatic pressure and the uniaxial stress.…”
Section: Introductionmentioning
confidence: 87%
“…The 1s impurity state is taken as ground level for D 0 and the 1p level of one electron system without the impurity is taken as the final state for D 0 as similar with previous studies. 6,[8][9][10][11]14 In order to calculate the numerical values of the photoionization cross-section given by Eq. ( 4), F ef f /F 0 is taken as approximately unity because the calculation of this quantity is very difficult and it has no effect on the photoionization cross-section shape [9][10][11][12] .…”
Section: A Theory Of Photoionization Cross-sectionmentioning
confidence: 99%
“…Although there are no experimental studies, the photoionization cross section of a hydrogenic impurity in low-dimensional quantum structures has been studied theoretically by many authors. [6][7][8][9][10][11][12][13][14] The cross section strongly depends on the impurity binding energy and its wave function. 8 The photoionization cross section is still studied extensively under different physical parameters (i.e electric field, magnetic field, hydrostatic pressure) in low-dimensional quantum nano structures.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the cross-section rises steeply at the threshold frequency and then decreases with photon frequency. Variational procedure was used to study the influence of an axial magnetic field and hydrostatic pressure on the binding energy and the impurity related photoionization cross-section in quantum wire [24,25]. The findings revealed that the photoionization crosssection strongly depends on the symmetry of the potential that confines the carriers.…”
Section: Introductionmentioning
confidence: 99%